A somatosensory circuit for cooling perception in mice - Milenkovic, Nevena; Zhao, Wen-Jie; Walcher, Jan; Albert, Tobias; Siemens, Jan; Lewin, Gary R.; Poulet, James F. A. (Nature neuroscience, 2014)
The temperature of an object provides important somatosensory information for animals performing tactile tasks. Humans can perceive skin cooling of less than one degree, but the sensory afferents and central circuits that they engage to enable the perception of surface temperature are poorly understood. To address these questions, we examined the perception of glabrous skin cooling in mice. We found that mice were also capable of perceiving small amplitude skin cooling and that primary somatosensory (S1) cortical neurons were required for cooling perception. Moreover, the absence of the menthol-gated transient receptor potential melastatin 8 ion channel in sensory afferent fibers eliminated the ability to perceive cold and the corresponding activation of S1 neurons. Our results identify parts of a neural circuit underlying cold perception in mice and provide a new model system for the analysis of thermal processing and perception and multimodal integration.
Gesehen am 05.02.2021